TRANSLATION SHIFTS OF THE ENGLISH PHRASES IN TAYLOR SWIFT’S SONGS INTO INDONESIAN - Ika Putri, Ni Putu Winta; Widiastuti, Ni Made Ayu; Saientisna, Made Detriasmita (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
Abstract             This paper aims to find out the types of translation shifts occurring in the translation of phrases in Taylor Swift’s song lyrics from English into Indonesian, and to describe the types of equivalence in their translation. The data sources of this research are the English Taylor Swift’s song lyrics and their translations in Indonesian taken from the music videos which contain lyrics in English and translations in Indonesian appeared on the screen. The playlists were downloaded from a YouTube channel called Indolirik. To obtain the data necessary for the discussion, the documentation method was applied. The data were analyzed qualitatively based on types of translation shifts (Catford, 1965), and the types of translation (Nida and Taber, 1982). The analysis shows that all types of shifts except intra-system shifts occur in English-to-Indonesian translations, with unit shifts being the most frequent, reflecting significant structural and linguistic adjustments. Formal correspondence was applied more frequently compared to dynamic equivalence. It is because from the total of 106 data used, the number of simple phrases was found more dominant (103 data) than the complex phrases (3 data). Simple phrases are usually more to the point or direct when translated compared to complex phrases.   Keywords: English-Indonesian translation, translation shifts, phrases, types of equivalence                                                                                                                                        Abstrak             Tulisan ini bertujuan untuk mengidentifikasi jenis-jenis pergeseran terjemahan frasa dalam lirik lagu Taylor Swift dari bahasa Inggris ke bahasa Indonesia, dan menganalisis jenis-jenis kesepadanan pada terjemahannya. Sumber data penelitian ini adalah lirik lagu Taylor Swift dalam bahasa Inggris dan terjemahannya dalam bahasa Indonesia. Lirik lagu didapatkan dari video musik pada Playlist yang diunduh dari saluran YouTube bernama Indolirik . Data dikumpulkan dengan menerapkan metode dokumentasi. Data yang telah dikumpulkan dianalisis dengan metode kualitatif-deskriptif. Pertama, data dianalisis berdasarkan jenis pergeseran terjemahan (Catford, 1965), dan kemudian berdasarkan jenis kesepadanan terjemahan (Nida dan Taber, 1982). Analisis menunjukkan bahwa semua jenis pergeseran kecuali pergeseran intra-sistem ditemukan dalam terjemahan bahasa Inggris-ke-Indonesia pada data, dengan pergeseran unit menjadi yang paling banyak ditemukan. Hal ini menunjukkan adanya penyesuaian struktur frasa yang signifikan. Formal correspondence lebih sering digunakan dibandingkan dengan dynamic equivalence . Hal ini dikarenakan dari total 106 data yang digunakan, jumlah frasa sederhana ditemukan lebih dominan (103 data) daripada frasa kompleks (3 data). Frasa sederhana biasanya diterjemahkan secara langsung atau to the point / direct dibandingkan dengan frasa kompleks.   Kata Kunci: terjemahan Bahasa Inggris-Indonesia, pergeseran pada terjemahan, frasa, tipe kesepadanan